The ableism elephant in the academy: a study examining academia as informed by Australian scholars with lived experience. Issue 7 (14th September 2019) - Mellifont, Damian; Smith-Merry, Jennifer; Dickinson, Helen; Llewellyn, Gwynnyth; Clifton, Shane; Ragen, Jo; Raffaele, Martin; Williamson, Paul
Abstract: The academy should be a welcoming environment for people with disability. Across Australia, however, there is a current shortage of programmes supporting people with disability to develop their careers as researchers. This article critically investigates current practice and experiences concerning universities and the employment and career development of people with disability as advised by the literature, and how this practice aligns with the lived experiences of several of our authors. Our review of the literature utilising Scopus, PsycINFO and ProQuest databases found a deficiency of research attention on this topic, with only 16 relevant articles identified. This paucity of literary evidence has been augmented in the article by personal stories shared by four of its authors. By focusing on evidence-based measures with potential to support disability employment and career pathways throughout universities in Australia and elsewhere, this article challenges leaders to address ableism and to advance a more inclusive academy.